Analisis Deskriptif Manajemen Redaksional Surat Kabar Lokal Radar Sumbawa Ditengah Arus Media Online - Lila Fadilah Kusuma; M. Syukron Anshori (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2021)
Descriptive Analysis of the Editorial Management of Local Newspaper namely Radar Sumbawa amidst the Flow of Online Media Information explosion is a real problem in nowadays rapidly developing computerized era. Increasingly tighter competition makes various fields of information media to be able to maintain their existence by presenting interesting and actual news. One of the solutions is by implementing directed editorial management. The basic functions of management consist of four, namely POAC which stands for Planning, Organizing, Actuating, and Controlling. This study aimed to determine how the implementation of POAC management in the editorial of Radar Sumbawa, both in printed and online media. The approach used in this research is a qualitative approach and the data collection techniques used were interview, observation, and documentation. From the research results, it is obtained that the POAC management applied to the editorial of Radar Sumbawa newspaper has been implemented properly in accordance with POAC guidelines, namely by holding projection and evaluation meetings to plan coverage, evaluate, select professional human resources (HR) in their fields, and hold training for journalists to further hone their skills. Radar also pays attention on the needs of people involved in the editorial sector, such as giving rewards to outstanding journalists and all other facilities that can support their activities. Meanwhile, the POAC management applied to the editorial website of Radar is also not much different from the printed media. The Radar Sumbawa website is well functioning and posts news regularly. This returns to the principle of Radar Sumbawa, which is to become the largest newspaper and a reference for the people of West Nusa Tenggara. Keywords: Editorial Managemnt, Local Newspaper, Online Media